THE EFFECT OF ENTREPRENEURSHIP EDUCATION, LOCUS OF CONTROL AND THE NEED FOR ACHIEVEMENT ON ENTREPRENEURSHIP INTENTIONS OF UNDERGRADUATE STUDENTS FACULTY OF ECONOMICS AND BUSINESS FOR THE CLASS OF 2017 RIAU UNIVERSITY - Samjess, Pretty; Marzolina, Marzolina; Fitri, Kurniawaty (Program Pascasarjana, Universitas Riau, 2022)
This study aims to determine the effect of entrepreneurship education, locus of control, and need for achievement on the entrepreneurial intentions of undergraduate students at the Faculty of Economics and Business, Riau University. The population in this study is the active undergraduate student class of 2017. The sampling technique was the purposive sampling method (85 students from 562 students based on criteria). To prove the study's findings, primary data were collected in this study using a questionnaire as a research instrument. Multiple regression analysis by the SPSS program was used to test the hypothesis in this study. The results show that: 1) there is an effect of entrepreneurship education on the entrepreneurial intentions of undergraduate students; 2) there is an effect of locus of control on the entrepreneurial intentions of undergraduate students; 3) there is an effect of the need for achievement on the entrepreneurial intentions of undergraduate students; and 4) there is an effect simultaneously of entrepreneurship education, locus of control, and the need for achievement on the entrepreneurial intentions of undergraduate students.